Analisis Pemanfaataan Dana Bantuan Operasional Kesehatan (BOK) di Puskesmas Jetak Kabupaten Semarang - Putri, Sefira Salsabila; Jati, Sutopo Patria; Fatmasari, Eka Yunila (Jurnal Kesehatan Masyarakat (Undip), 2020)
This study aims to determine the utilization of health operational assistance funds in Semarang district Jetak health center. The research design used was descriptive analytic research. This research was carried out by conducting in-depth interviews with 6 informants involved in the utilization of health operational aid funds at the health center in Jetak District, Semarang. Data collection techniques used are in-depth interviews and document review. The data analysis technique consists of four stages, namely data collection, data reduction, data presentation and conclusion drawing. Validity test data used is the source triangulation method. The results showed that indicators of budgetary participation in the utilization of health operational aid funds in jetak health centers were not good because there was no effective leadership. For indicators of budget target clarity it is already good because it is in accordance with the technical guidelines and lattices of the Semarang district health office. Then the budget evaluation indicators are still lacking because the mini workshop has not been optimally implemented. Whereas indicators for budget target difficulties are also lacking because there is no proper roadmap and planning yet.